2013
DOI: 10.1097/mpg.0b013e318291fec5
|View full text |Cite
|
Sign up to set email alerts
|

Bone Deficits in Parenteral Nutrition–Dependent Infants and Children With Intestinal Failure Are Attenuated When Accounting for Slower Growth

Abstract: Objective To determine if bone mineral content (BMC) and density (BMD) of infants and children with parenteral nutrition (PN)-dependent intestinal failure (IF) is lower than healthy controls, and investigate potential causes of lower BMC and BMD. Methods We performed a cross-sectional study comparing infants and children with PN-dependent IF with duos of age, sex, and race matched controls. Lumbar spine BMC and BMD were measured by dual energy x-ray absorptiometry, and serum cytokines, aluminum, IGF-1, insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 48 publications
0
37
2
Order By: Relevance
“…2). This is different from another study of paediatric IF patients on PN where a normal value of 1,25(OH)2D was found [43]. Lower 1,25(OH) 2 D level raises questions regarding the mechanism.…”
Section: Median (25e75 Percentile)contrasting
confidence: 88%
See 1 more Smart Citation
“…2). This is different from another study of paediatric IF patients on PN where a normal value of 1,25(OH)2D was found [43]. Lower 1,25(OH) 2 D level raises questions regarding the mechanism.…”
Section: Median (25e75 Percentile)contrasting
confidence: 88%
“…However, no difference was found for healthy participants included during MarcheJune compared to AugusteSeptember. Other studies have reported vitamin D insufficiency in 20e68% of paediatric IF patients [12,13,33,34,36,37,41,42], which is more than the 5% found by Appleman et al [43], and the 10% found in the present study. An explanation could be that these studies also included patients weaned off PN, and hence their absorption could be compromised.…”
Section: Median (25e75 Percentile)contrasting
confidence: 63%
“…For patients who are PN dependent long term, body composition is often abnormal with significant deficit in limb lean mass [62]. Metabolic bone disease is related to aluminium contaminating fluids, low serum vitamin D and insulin-like growth factor, and inflammation [63]. Bone mineral density is reduced particularly in children with congenital enterocyte disorders or severe dysmotility [64].…”
Section: Pn Monitoringmentioning
confidence: 99%
“…Previous studies reported that children with IF are significantly lighter and shorter than healthy chidren. [2][3][4][5] One study assessing body composition showed that they have a lower FFM. 3 In addition, fully PN-dependent patients had increased FM.…”
Section: Introductionmentioning
confidence: 99%